Citrus aurantium Naringenin Prevents Osteosarcoma Progression and Recurrence in the Patients Who Underwent Osteosarcoma Surgery by Improving Antioxidant Capability. (7th February 2018) - Zhang, Lirong; Xu, Xiaohua; Jiang, Tiechao; Wu, Kunzhe; Ding, Chuanbo; Liu, Zhen; Zhang, Xuanhe; Yu, Tianhua; Song, Changlong
Abstract : Citrus aurantium is rich in flavonoids, which may prevent osteosarcoma progression, but its related molecular mechanism remains unclear. Flavonoids were extracted from C. aurantium and purified by reparative HPLC. Each fraction was identified by using electrospray ionisation mass spectrometry (ESI-MS). Three main components (naringin, naringenin, and hesperetin) were isolated from C. aurantium . Naringenin inhibited the growth of MG-63 cells, whereas naringin and hesperetin had no inhibitory function on cell growth. ROS production was increased in naringin- and hesperetin-treated groups after one day of culture while the level was always lowest in the naringenin-treated group after three days of culture. 95 osteosarcoma patients who underwent surgery were assigned into two groups: naringenin group (NG, received 20 mg naringenin daily, n = 47 ) and control group (CG, received 20 mg placebo daily, n = 48 ). After an average of two-year follow-up, osteosarcoma volumes were smaller in the NG group than in the CG group (P > 0.01 ). The rate of osteosarcoma recurrence was also lower in the NG group than in CG group. ROS levels were lower in the NG group than in the CG group. Thus, naringenin from Citrus aurantium inhibits osteosarcoma progression and local recurrence in the patients who underwent osteosarcoma surgery by improving antioxidant capability.